2013
DOI: 10.1007/s00705-013-1767-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic properties of endemic Chinese porcine epidemic diarrhea virus strains isolated since 2010

Abstract: Acute diarrhea outbreaks caused by porcine epidemic diarrhea virus (PEDV) have been observed in various pig-breeding provinces of China since December 2010. Endemic strains of PEDV were isolated from different areas, and the complete genome sequences of 10 isolates were determined. Our objective in this study was to genetically characterize current Chinese field isolates of PEDV to better understand their epidemiology and genetic diversity. Sequence analysis showed that 10 post-2010 isolates shared high homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…Although PEDV infection still affected Chinese pig farms before 2010, it was sporadic and regional. No large-scale epidemic occurred until an outbreak, clinically characterized by acute diarrhea, originated in the southern provinces in October 2010, and soon swept throughout the country Sun et al, 2012;Tian et al, 2014;Wang et al, 2013;Sun et al, 2015a). The mortality rate of PED among piglets soared to 80%-100%, and the pig farming industry suffered a destructive blow (Sun et al, 2012).…”
Section: Ped History In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Although PEDV infection still affected Chinese pig farms before 2010, it was sporadic and regional. No large-scale epidemic occurred until an outbreak, clinically characterized by acute diarrhea, originated in the southern provinces in October 2010, and soon swept throughout the country Sun et al, 2012;Tian et al, 2014;Wang et al, 2013;Sun et al, 2015a). The mortality rate of PED among piglets soared to 80%-100%, and the pig farming industry suffered a destructive blow (Sun et al, 2012).…”
Section: Ped History In Chinamentioning
confidence: 99%
“…The disease had a death toll of over one million piglets in South China, with devastating damage to the pig industry. Even vaccinated suckling piglets were not spared, and the morbidity and mortality rates were almost 100% Sun et al, 2012;Wang et al, 2013). The affected piglets predominantly showed yellow watery stools, weight loss, and death from dehydration.…”
Section: Pedv Prevalence In Chinamentioning
confidence: 99%
“…The disease is characterized by severe diarrhea, vomiting, dehydration, and death, and has a mortality rate among suckling piglets of more than 90 % (Lee, 2015). Porcine epidemic diarrhea virus (PEDV), the causative agent of PED, is a RNA virus belonging to the alpha genus of the coronavirus family (Wang et al, 2013). The spike(S) protein is the primary target for development of subunit vaccines against PEDV.…”
Section: Introductionmentioning
confidence: 99%
“…67 The results of many studies based on sequencing and phylogenetic analyses showed that these PEDV isolates with high virulence circulating in the People's Republic of China were new variants and differed genetically from the prototype CV777 strain. 11,59,[67][68][69][70][71][72][73][74][75][76][77][78] Now, PED became endemic; however, it remains the most devastating enteric disease leading to serious losses in the People's Republic of China. PED outbreaks in the People's Republic of China from late 2010 were caused by at least three genotypes, including genotypes IIa, IIb, and Ib.…”
Section: Asiamentioning
confidence: 99%